2011
DOI: 10.1093/hmg/ddr196
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of α-actinin-3 is associated with increased susceptibility to contraction-induced damage and skeletal muscle remodeling

Abstract: Sarcomeric α-actinins (α-actinin-2 and -3) are a major component of the Z-disk in skeletal muscle, where they crosslink actin and other structural proteins to maintain an ordered myofibrillar array. Homozygosity for the common null polymorphism (R577X) in ACTN3 results in the absence of fast fiber-specific α-actinin-3 in ∼20% of the general population. α-Actinin-3 deficiency is associated with decreased force generation and is detrimental to sprint and power performance in elite athletes, suggesting that α-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(133 citation statements)
references
References 72 publications
8
120
0
5
Order By: Relevance
“…To detect muscle damage, Martínez-Amat et al (2005 and Vincent et al (2010) suggest the use of speciWc markers of skeletal muscle which has a quick release and high sensitivity, such as the -actin. The results showed that indicators of muscle damage (CK activity and -actin concentrations) are generally higher in ACTN3XX individuals post-eccentric training in accordance with previous studies (Vincent et al 2010;Seto et al 2011). This Wnding is in contrast with Clarkson et al (2005) and Chan et al (2008).…”
Section: Discussionsupporting
confidence: 90%
“…To detect muscle damage, Martínez-Amat et al (2005 and Vincent et al (2010) suggest the use of speciWc markers of skeletal muscle which has a quick release and high sensitivity, such as the -actin. The results showed that indicators of muscle damage (CK activity and -actin concentrations) are generally higher in ACTN3XX individuals post-eccentric training in accordance with previous studies (Vincent et al 2010;Seto et al 2011). This Wnding is in contrast with Clarkson et al (2005) and Chan et al (2008).…”
Section: Discussionsupporting
confidence: 90%
“…According to Warren et al,65 degradation of contractile proteins may further contribute to strength loss during prolonged (>72 h) muscle injury. Although evidence implicates various other structural and contractile proteins, such as α-actinin-3, in strength loss following damaging exercise,71,72 more research is needed in order to understand the mechanical aspect of their contribution.…”
Section: Mechanisms and Consequencesmentioning
confidence: 99%
“…It is important to note that, although the loss of ACTN3 has been observed in muscular dystrophies (107), within healthy populations this has no impact on muscle force and power due to compensation from ACTN2 and desmin (75,99).…”
Section: E3 Force Transfer In Skeletal Musclementioning
confidence: 99%